1988
DOI: 10.1210/endo-123-4-1928
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Role of Growth Hormone (GH)-Releasing Factor and Somatostatin in the Dynamics of GH Secretion in Adult Male Rat

Abstract: To investigate the physiological role of GRF and somatostatin (SRIF) in GH secretion in adult male rats, we prepared in vitro models using the perifusion system of cultured rat anterior pituitary cells exposed to various combinations of human GRF-(1-44)NH2 (hGRF) and SRIF. We studied the following three models on GRF secretion: 1) pulsatile GRF secreted at 1-h intervals, 2) pulsatile GRF secreted at 3-h intervals, and 3) GRF continuously secreted. When 5-min pulses of 20 nM GRF were delivered at 1-h intervals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
12
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 29 publications
5
12
0
Order By: Relevance
“…The pulsatile secretion of GH is regulated by the reciprocal interplay of hypothalamic GHRH and somatostatin (32)(33)(34)(35) and by responsivity of the somatotrope cells to these regulatory peptides (28). In general, the amount of GHRH released at any given level of somatostatin tone determines the amount of GH released per secretory episode, and the pattern of somatostatin action determines the frequency and duration of the GH secretory bursts (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The pulsatile secretion of GH is regulated by the reciprocal interplay of hypothalamic GHRH and somatostatin (32)(33)(34)(35) and by responsivity of the somatotrope cells to these regulatory peptides (28). In general, the amount of GHRH released at any given level of somatostatin tone determines the amount of GH released per secretory episode, and the pattern of somatostatin action determines the frequency and duration of the GH secretory bursts (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that this attenuation of the G H response can be attributed to remnant endogenous SRIF secretion, because Arsenijeric et al (30) have reported that transient desenstization to repeated G R F pulses was observed in rats which were passively immunized against SRIF. In addition, we have found that desensitization to multiple G R F pulses can be observed even in a rat anterior pituitary perifusion system in which the effect of SRIF is excluded (10). Therefore, it is thought that the diminishing response to repeated G R F injections found in the present study was attributable to either depletion of the releasable intracellular G H pool or to impairment of the G R F receptor such as by downregulation (31).…”
Section: Discussionmentioning
confidence: 45%
“…Recently, there has been much interest in the hypothalamic interactions between G R F and SRIF (8, 9), but the pituitary interactions between these two peptides occurring during G H secretion still remain unclear. We previously investigated the dynamic relationship between G R F and SRIF in the regulation of pulsatile GH secretion in a perifusion system using cultured rat anterior pituitary cells (10). Our data suggested that prolonged pre-exposure to SRIF could prevent an attenuated response to repeated GRF pulses, and that co-exposure to continuous SRIF with brief pauses and hourly GRF pulses could produce large GH surges.…”
mentioning
confidence: 85%
“…Considerable evidence indicates that T3 stimulates the GH gene transcription and subsequently increases GH secretion [1][2][3]. Although it is also established that pulsatile GH secretion is mediated by hypothalamic GRH and somatostatin secretion [15][16][17], the stimulatory action of thyroid hormone on GH secretion occurs at the pituitary level rather than at the hypothalamic level [18,19]. Serum IGF-I levels were not significantly different from normal in hyperthyroid patients despite the increase in urinary GH.…”
Section: Discussionmentioning
confidence: 99%